Destroying a Kerr Black Hole - N. S. Risdianto; M. F. Rosyid (JPSE (Journal of Physical Science and Engineering), 2017)
Based on three fundamentals aspects presented by Penrose, Wald, and Hawking, the black hole’s destroying scenario can be made. The main problem of this destroying process is about the presence of black hole’s angular momentum and charge. Especially for this research which is only taking an action into a rotating uncharged black hole (Kerr Black Hole). This research showed that in order to destroy a Kerr Black Hole (especially  a near-extremal Kerr Black Hole) , one needs to remove its angular momentum instead by forcing  it in extremal conditions and  let Hawking Radiation  occurs. On the other hand, the research showed that particle’s mass is linearly dependant in Penrose Process. The result also showed (which ;  is a black hole’s angular momentum and  is a black hole mass) cannot be reached because only black hole with negative net-energy can fulfil the condition. In another side,  we calculated the minimum power needed by hole to kick the particles out.DOI: http://dx.doi.org/10.17977/um024v2i12017p007